Pengembangan Penuntun Praktikum Fisika SMA/MA Berbasis KPS menggunakan 3D Pageflip Professional pada Materi Pengukuran - Retno Wulan Darii; Sri Purwaningsih; Darmaji Darmaji (Universitas Negeri Jakarta, 2021)
The purpose of this study was to develop and test the feasibility of a practical science process skills-based practical guide using 3D Pageflip Professional measurement material. This type of research is research and development with the ADDIE model. The instrument used was a material and media validation questionnaire and a student perception questionnaire. The data analysis technique in the form of suggestions from the validator was carried out descriptively qualitatively. The practicum guide that has been developed has an .exe format that can be run on a PC / laptop. This practicumm guide has been validated and declared valid with an average score of material experts of 3.9 which is categorized as very good and an average score of media experts of 3.4 which is classified as in the very good category. Furthermore, the score of the students' perceptions of the practicum guide was 3.5 which was in the very good category. The advantages contained in the practicum guide developed are that the language used is easy to understand, the video displayed is three-dimensional, there are complementary experiments that can be used for distance learning, easy to operate.